Comparative assessment of the quality of age-at-event reporting in three HIV cohort studies in sub-Saharan Africa. (23rd March 2009) - Wringe, A; Cremin, I; Todd, J; McGrath, N; Kasamba, I; Herbst, K; Mushore, P; Żaba, B; Slaymaker, E
Abstract : Objectives: To assess inconsistencies in reported age at first sex (AFS) and age at first marriage (AFM) in three African cohorts, and consider their implications for interpreting trends in sexual and marital debut. Methods: Data were analysed from population-based cohort studies in Zimbabwe, Uganda and South Africa with 3, 10 and 4 behavioural survey rounds, respectively. Three rounds over a similar time frame were selected from each site for comparative purposes. The consistency of AFS and AFM reports was assessed for each site by comparing responses made by participants in multiple surveys. Respondents were defined as unreliable if less than half of all their age-at-event reports were the same. Kaplan-Meier functions were used to describe the cumulative proportion (1) having had sex and (2) married by age, stratified by sex, birth cohort and site, to compare the influence of reporting inconsistencies on these estimates. Results: Among participants attending all three comparable rounds, the percentage with unreliable AFS reports ranged from 30% among South African women to 56% among Zimbabwean men, with similar patterns observed for AFM. Inclusion of unreliable reports had little effect on estimates of median age-at-event in all sites. There was some evidence from the 1960–9 birth cohort that women in Uganda and both sexes in South Africa reported later AFS as they aged. Conclusion: Although reporting quality is unlikely to affect comparisons of AFS and AFM between settings, care should be taken not to overinterpret small changes in reported age-at-event over time within each site.